Prevalence and clinical characteristics of metabolically healthy obese versus metabolically unhealthy obese school children - Wan Mohd Zin, Ruziana Mona; Jalaludin, Muhammad Yazid; Yahya, Abqariyah; Nur Zati Iwani, Ahmad Kamil; Md Zain, Fuziah; Hong, Janet Yeow Hua; Mokhtar, Abdul Halim; Wan Mohamud, Wan Nazaimoon (Frontiers in Endocrinology, 2022)
Introduction: Obese children with the absence of traditional cardiometabolic risk factors (CRF) have been described as metabolically healthy obese (MHO). The MHO children have a favorable metabolic profile with normal glucose metabolism, lipids, and blood pressure compared to the metabolically unhealthy obese (MUO) children. This study aimed to compare several parameters related to obesity between these two groups and to examine the predictors associated with the MHO phenotype. Methods: This study included a cross-sectional baseline data of 193 obese children (BMI z-score > +2 SD) aged 8-16 years enrolled in MyBFF@school program, a school-based intervention study conducted between January and December 2014. Metabolic status was defined based on the 2018 consensus-based criteria with MHO children had no CRF (HDL-cholesterol > 1.03 mmol/L, triglycerides ≤ 1.7 mmol/L, systolic and diastolic blood pressure ≤ 90th percentile, and fasting plasma glucose ≤ 5.6 mmol/L). Those that did not meet one or more of the above criteria were classified as MUO. Results: The prevalence of MHO was 30.1% (95% CI 23.7 – 37.1) among obese schoolchildren and more common in younger and prepubertal children. Compared to MUO, MHO children had significantly lower BMI, smaller waist circumference, lower uric acid, higher adiponectin, and higher apolipoprotein A-1 levels (p < 0.01). Multivariate logistic regression showed that adiponectin (OR: 1.33, 95% CI 1.05 - 1.68) and apolipoprotein A-1 (OR: 1.02, 95% CI 1.01 – 1.03) were independent predictors for MHO phenotype in this population. Conclusions: MHO was more common in younger and prepubertal obese children. Higher serum levels of adiponectin and apolipoprotein A-1 increased the possibility of obese schoolchildren to be classified into MHO phenotype.